A fluorescent porous covalent-organic polymer (COP-3) for highly selective and sensitive detection of Fe3+ in aqueous solution. (22nd January 2021) - Zhang, Han; Ding, Guan-yu; Cui, Dong-xu; Yousaf, Afifa; Chen, Li; Wang, Xin-Long; Shan, Guo-Gang; Sun, Chun-Yi; Su, Zhong-Min
Abstract : A novel COP exhibits excellent performance in sensing Fe 3+ at the ppb level, with high cyclicity and anti-interfere ability. Abstract : A TPE-based fluorescent porous covalent organic polymer (COP-3) was designed and synthesized. The COP-3 exhibits excellent performance in sensing Fe 3+ with high anti-interference, recyclability and a low limit of detection (LOD) of 0.191 μM (10.696 ppb), which is much lower than those of the reported metal-free porous polymers.